Monarchical experiences in the Greek World: the Mycenaean and Homeric cases - André, Alessandra (Romanitas - Revista de Estudos Grecolatinos, 2017)
Although discourses from the world of polis relegated monarchy to a typology of government far from the Greeks, and to reduce the importance of it, the truth is that this system of government was present at various points during the political history of Greece. Different nomenclatures like, anax, basileus, king or tyrannos, represent that form of government that reunited in the hands of a single man the political power. In this article, we will analyze generally two of these monarchies, the Mycenaean and the Homeric, focusing on the image of the king. From the figure of the anax and the Homeric basileus, our main objective is to establish a comparative picture between the first two forms of Greek kingship.
Keywords: Greece; Monarchy; Mycenaean period; Anax; Homeric basileus